Critique and Erasure: Responding to Eppley's "Reading Mastery as Pegagogy of Erasure" - Siegfried Engelmann (Journal of Research in Rural Education, 2011)
Karen Eppley's commentary (2011) on Dr. Stockard's article, "Increasing Reading Skills in Rural Areas: An Analysis of Three Rural School Districts" (Stockard, 2011), uses selected details as points of departure for a critique of Reading Mastery, a structured reading curriculum used at the elementary level. The arguments and conclusions proffered by Eppley have a critical problem, however. They are not merely unsupported by facts; they generate conclusions that are the opposite of what the facts show.